Philosophy and education in disobedient poetic practices in obediencene (Revista Apotheke, 2024)
This article discusses the concept of [dis]obedience based on the relationship between philosophy and education in disobedient poetic practices in undergraduate Arts courses. The objective is to deal with the possibility of proposing a more performative way of discussing and practicing philosophy based on artistic approaches that can be seen as transgressors in order to escape the society of contemporary subtle control based on the presence of bodies and common practices. In the first section of the text, we show how the concept of [dis]obedience appears in different authors, we show the relationship of philosophical and poetic approaches to disobedient forms of life and we expose how contemporary art offers subsidies for this. In the second section, we propose a critical and descriptive imagery analysis of photo records of extension activities promoted at a university, connecting them to the notion of transgressive teaching and presenting ways of putting disobedient forms of life into practice through speculative and poetic activities that converge to the formation of commons.
Keywords: philosophy and education; control society; disobedient poetic; [Dis]obedience; transgressive education